L7 PH11003 22dec
L7 PH11003 22dec
L7 PH11003 22dec
https://www.phy.olemiss.edu/~perera/animations/waves.html
Longitudinal wave: The particle in a medium oscillates back and forth
about their equilibrium position but it is the disturbance which travels
NOT the individual particles in the medium.
(We are neglecting frictional effects—in a real rope, the bump gradually
gets smaller as it moves along.)
Longitudinal wave in a rod (elastic medium)
How disturbance evolve?
𝑥 𝑥 + Δ𝑥
𝑥 𝑥 + Δ𝑥
If disturbance is created in a rod of density ρ and area of cross-section A, it
propagate as a linear chain of spring-mass system in the continuum limit:
∂2 ξ
At a position x, force equation of slab : F = ρ A∆ x 2
∂t
( It is simply mass times acceleration )
Consider a linear chain of identical spring and masses. The displacement of
jth mass satisfy the equation of motion
k k k
m m m m
ξ j−1 (t ) ξ j (t ) ξ j+1 (t )
m ξj (t ) = −k (ξ j − ξ j +1 ) − k (ξ j − ξ j −1 )
[ξ j +1 ]
(t ) − ξ j (t ) → [ξ ( x + ∆ x, t ) − ξ ( x, t )]
∂ ξ ( x, t ) ( ∆ x ) 2 ∂ 2 ξ ( x, t )
= ξ ( x, t ) + ∆ x + ... − ξ ( x, t )
∂x 2 ∂x 2
∂ ξ ( x, t ) ( ∆ x ) 2 ∂ 2 ξ ( x, t )
=∆x +
∂x 2 ∂ x2
[ξ (t ) − ξ
j j −1 ]
(t ) → [ξ ( x, t ) − ξ ( x − ∆ x, t )]
∂ ξ ( x, t ) ( ∆ x ) 2 ∂ 2 ξ ( x, t )
= ξ ( x, t ) − ξ ( x, t ) + ∆ x − ...
∂x 2 ∂x 2
∂ ξ ( x, t ) ( ∆ x ) 2 ∂ 2 ξ ( x, t )
=∆x −
∂x 2 ∂ x2
Implies,
[ξ j +1 ] [ ]
(t ) − ξ j (t ) − ξ j (t ) − ξ j −1 (t ) =
∂ ξ ( x, t ) ( ∆ x ) 2 ∂ 2 ξ ( x, t ) ∂ ξ ( x, t ) ( ∆ x ) 2 ∂ 2 ξ ( x, t )
= ∆ x + −∆x −
∂ x 2 ∂ x 2
∂ x 2 ∂ x 2
∂ 2
ξ ( x, t )
= (∆ x) 2
∂ x2
Y A Y A
The force in terms of Y F = ξ = ∆ξ = k ∆ξ
L ∆x
Δ𝜉
Here, is the local strain.
Δ𝑥
m ξj (t ) = −k (ξ j − ξ j +1 ) − k (ξ j − ξ j −1 )
∂ 2 ξ ( x, t ) Y A 2 ∂ ξ ( x, t )
2
ρ A∆ x = ( ∆ x)
∂t 2
∆x ∂ x2 Y
c =
2
∂ ξ ( x, t ) Y ∂ ξ ( x, t )
2 2
∂ ξ ( x, t ) 1 ∂ ξ ( x, t )
2 2 s
ρ
= ⇒ = 2
∂t 2
ρ ∂x 2
∂x 2
cs ∂t2
∂ 2 ξ ( x, t ) B ∂ 2 ξ ( x, t ) ∂ 2 ξ ( x, t ) 1 ∂ 2 ξ ( x, t )
= ⇒ = 2
∂t 2
ρ ∂x 2
∂x 2
cB ∂ t 2
Where B is the bulk modulus of the fluid
B
c =
2
ρ
B
f ( x − c t ) and f ( x + c t )
So, the two aspects of the set of wave equation
f (x ± c t)
∂ 2 ξ ( x, t ) 1 ∂ 2 ξ ( x, t )
= 2
∂x 2
c ∂t2
∆x T
Consider an element of the string
between x and x + ∆x
For a small displacement y, we can assume that the magnitude of the tension T remain
the same, but acts in different direction at the two ends of the elements of the string.
This give rise to a net vertical force.
The forces on the bit of string (neglecting the tiny force of gravity, air resistance, etc.)
are the tensions T at the two ends. The tension will be uniform in magnitude along the
string, but the string curves if it’s waving, so the two T vectors at opposite ends of the
bit of string do not quite cancel, this is the net force we’re looking for.
y
T
𝜃 + Δ𝜃
𝑥 𝑥 + Δ𝑥 x
Fy = T sinθ x + ∆x
− T sinθ x
Fy = −T sin θ + T sin(θ + ∆θ )
for small θ , Fy ≈ T tanθ x + ∆x
− T tanθ x
for small θ ; Fy ≈ T ∆θ
∂ y ∂ y
Fy = T − dm y = T ∆θ ⇒ ( µ ∆ x) y = T ∆θ
∂ x x + ∆x ∂ x x ∂y 1 ∂θ ∂2 y
tan θ = ⇒ = 2
∂ y ∂2 y ∂ y ∂2 y ∂ x cos θ ∂ x ∂ x
2
= T + ∆ x 2 − = T∆ x 2
∂ x x ∂ x ∂ x x ∂x
∂2 y ∂2 y
( µ ∆ x) 2 = T ∆θ = T∆x 2
∂2 y ∂2 y ∂t ∂x
dm y = µ ∆ x 2 = T∆ x 2
∂t ∂x 2
1 ∂ y ∂2 y
⇒ 2 2 = 2
c ∂t ∂x
1 ∂2 y ∂2 y
Wave Equation ⇒ 2 2 = 2
c ∂t ∂x
At the point x,
• The 1st derivative is the slope of the string.
• And, it’s this curvature that ensures the T’s at the two ends of a bit
of string are pointing along slightly different directions, and
therefore don’t cancel.
• This force, then, gives the mass times acceleration on the right.
Wave Equation
1 ∂2 y ∂2 y
⇒ 2 2 = 2
c ∂t ∂x
• All traveling waves move at the same speed and the speed is
determined by the tension and the mass per unit length.
f (x ± c t)
• Then sum of the two is also a solution to the equation: which is
superposition of the two.
Standing Waves from Traveling Waves
Standing waves on
a Stretched string
l
1 ∂2 y ∂2 y ⇒ y ( x, t ) = A cos(k x − ω t )
= 2
c ∂t
2 2
∂x ⇒ y ( x, t ) = A cos(− k x − ω t )
At, x = 0, y = 0 ⇒ A + B = 0
i (ω t − k x ) i (ω t + k x )
⇒ y ( x, t ) = A e − Ae
( )
= A ei ω t e −i k x − ei k x = − Aei ω t 2i sin( kx)
At x = l , y = 0
sin kl = 0, ⇒ kl = n π
iω t nπ
y ( x, t ) = − A(2i ) e sin x
l
iω t nπ
y ( x, t ) = − A(2i ) e sin x
l
(n-1) nodes between boundaries
This is standing wave
iω t nπ
y ( x, t ) = − A(2i ) e sin x
l
Wave equation for transverse wave
n
nth wavelength, l = λn On a string (both ends are fixed)
2
∂2 y 1 ∂2 y
or,ν n =
c nc
= = 2 2
λn 2 l ∂x 2
c ∂t
ωn x
⇒ y ( x, t ) = An sin cos ωnt ;
c
nπ T
where, ωn = = n ω1
L µ
December 28, 2020 21
Sinusoidal waves
They are
Progressive
Wave
t
December 28, 2020 23
x
New position of at
ω1 = ω + ∆ω , & ω2 = ω − ∆ω ,
k1 = k + ∆k , & k 2 = k − ∆k ,
Wave packet consist of individual waves whose
amplitude is modulated by an envelop
Speed of envelop=Group velocity (vg)
Speed of wavelets=Phase velocity (vp)
Non dispersive : All colored sphere moves with same speed
t0 t1 t2
Dispersive : Red sphere moves faster than blue sphere
Phase and Group velocity
Phase velocity follows straight line
Group velocity is
defined at a point by
the tangent at that
point
vg
P’
Non dispersive waves vp = Constant
Signal is propagated without distortion
More generally vp is a function of (or k)
Prism expt in 1st year lab
A + δm
sin
µ (λ ) = 2 µ 2 − µ1
ω=
A µ −1
sin
2